Estimating the Most Likely Extreme Nacelle Acceleration of a Floating Offshore Wind Turbine From Physical Model Tank Testing - McMillan, A; McDonald, A; Pillai, AC; Yuan, Z; Davey, T (American Society of Mechanical Engineers (ASME), 2024)
This is the author accepted manuscript. The floating platforms on which floating offshore wind tur bines are mounted introduce considerable complexity in terms of dynamic motion. Understanding the extreme response of these marine structures is important. One such extreme response is the nacelle accelerations, which can cause damage to nacelle components, such as the generator, and should therefore be kept to a minimum. Tank testing is a tool which can be used to under stand the behaviour of these structures, and to determine extreme response. Here, a method of estimating the most likely extreme nacelle accelerations from a tank testing programme is shown, using a 1:100 scaled model of the IEA 15 MW turbine with the Volturn-US semi-submersible platform. The results showed that the most likely extreme nacelle accelerations within the chosen 50-year return sea state are 0.195 g in the fore-aft direction, with a typical safety limit of 0.2-0.4 g. Extreme statistical analysis was carried out on the data obtained by a 3-DOF accelerometer, using the peaks-over-threshold (POT) method fitted to a generalised Pareto distribution (GPD). Threshold selection and declustering of data are also discussed. The results may be applied to further test programmes, aiding in the development and design of current or novel floating platforms in any programmable sea state Ministry for Business, Innovation and Employment Endeavour Fund Royal Academy of Engineering (RAE)